Strategi Dan Panduan Pemasaran Terhadap Toko Sabar Water Depot Air Minum Dengan Brosur Digital Melalui Instagram - Listia Nurjanah; Melina Melina (Universitas Internasional Batam, 2021)
Research at Sabar Water store has a purpose in helping to overcome problems in the form of achieving increased sales and increasing marketing sales products through social media channels, namely advertising on accounts owned by Sabar. This marketing application effort is carried out by establishing a procedure or implementation stage by the author who is then given explanation and follow-up work by employees of Sabar Water store. The implementation of this practice starts from October 10, 2020 until January 28. Data processing or data collection done by observation method and direct interview with the shop owner Sabar Water followed by design and implementation. The application of online marketing at the Sabar Water store includes creating an account on Instagram. The results of implementing this strategy indicate that there is a significant increase in buyers of product.